BareBone cloud IaaS: Revitalization disruptive technology - Soon, J.N.P. (Institute of Electrical and Electronics Engineers Inc., 2015)
With today's Internet of Hype-Things, technology innovation is no longer a strategic weapon to gain competitiveness or even sustainability at SME. Legacy frameworks are biased towards larger computing during happy day environment. This paper presents a new framework for SME to embrace IaaS with confidence to move up the value chain despite facing volatile economic turbulence. While disruptive BareBone cloud technology maybe inferior to large enterprises, holds potential opportunities to the smaller enterprise where base cost does matter. The use of three instruments (mass survey, interview and focus group) for collecting primary data has ensured consistent information validation. The findings from the directional correlation hypothesis affirm the negative correlation between infancy stage of technology innovation and the measurable organizational values expected by the small enterprise. This contribution can be applied during dilemma decision making stage for migrating into the next cloud computing infrastructure. Â© 2014 IEEE.